Oscillatory Cerebral Blood Flow Is Associated With Impaired Neurocognition and Functional Hyperemia in Postural Tachycardia Syndrome During Graded Tilt. Issue 3 (March 2015) - Stewart, Julian M.; Del Pozzi, Andrew T.; Pandey, Akash; Messer, Zachary R.; Terilli, Courtney; Medow, Marvin S.
Abstract : We hypothesize that upright cognitive impairment in patients with postural tachycardia syndrome (POTS) is caused by reduced cerebral blood flow (CBF). The CBF velocity (CBFv ) measured by transcranial Doppler ultrasound decreased excessively during 70° tilt in a minority of patients with intermittent hyperpnea/hypocapnia. Incremental tilt showed no difference in mean CBFv . But N-back memory tasking indicated progressive compromised memory, reduced functional hyperemia, and reduced neurovascular coupling. Orthostasis caused slow oscillations in CBFv linked to oscillations in arterial pressure in patients with POTS. We also hypothesize that oscillatory CBFv degrades neurovascular coupling. We performed 2-back testing when subjects were in supine position and during incremental tilts to 15°, 30°, 45°, and 60° in 11 patients with POTS and 9 controls. Oscillatory arterial pressure, oscillatory CBFv, and neurovascular coupling were similar in supine position. The oscillatory arterial pressure increased by 31%, 45%, 67%, and 93% in patients with POTS during tilt and remained unchanged in the controls. Oscillatory CBFv increased by 61%, 82%, 161%, and 264% in patients with POTS during tilt and remained unchanged in the controls. Functional hyperemia decreased from 4.1% to 3.0%, 1.1%, 0.2%, and to 0.04% in patients with POTS, but it was unchanged at 4% in the controls. Percent correct N-back responses decreased from 78% to 33% in patients with POTS, whereas they remained at 89% in the controls. In patients with POTS, oscillatory CBFv was linearly correlated with functional hyperemia ( r 2 =0.76). Increased oscillatory CBF is associated with reduced neurovascular coupling and diminished cognitive perf ormance in patients with POTS. Abstract : Supplemental Digital Content is available in the text.